An introduction to passive radar - Griffiths, H. (Hugh), 1956-; Baker, Christopher J. (Radar specialist) (Artech House, 2022)
This bestselling book - now in its second edition - introduces the basic principles of passive radar technology and provides a comprehensive overview of the recent developments and advances in this field. It shows you how passive radar works, how it differs from the active type, and helps you understand the benefits and drawbacks of this novel technology. The book gives you the knowledge you need to get a full understanding of this fascinating technology. All chapters have been fully revised and updated and are written in a clear and accessible style. New chapters have been added to cover advances in the technology that have already been built and demonstrated, including systems on moving platforms (aircraft and UAVs), as well as advances in types of transmission - notably single-frequency broadcast transmissions, and 5G - and in processing techniques. This book remains an important resource for engineers working in academic, industry, or government research laboratories; academics teaching graduate level students; and those working in the specification and procurement of radar systems who need to understand the performance and limitations of the technology.